INCIDENCE AND VIRULENCE TRAITS OF CANDIDA DUBLINIENSIS ISOLATED FROM CLINICALLY SUSPECTED PATIENTS - Vinodhini, Raja; Moorthy, Kannaiyan; Suresh, Mickymaray (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Fungal infections are caused by Candida species are increasing mainly in immunocompromised patients. Among Candida species, Candida dubliniensis has recently increasing opportunistic pathogenic yeast. The present study was aimed to assess the incidence and virulence factors of C. dubliniensis isolated from urine samples of various hospitalized clinically suspected patients. Methods: Totally 1,406 urine samples were processed, among that 9(0.64%) were identified as C. dubliniensis by germ tube production, biochemical test (Candida identification kit), CHROM agar Candida differential medium and growth at 45°C. Virulence factors of the C. dubliniensis viz., phospholipase, proteinase, esterase, lipase, haemolysin and biofilm production were detected by standard procedures. Results: Maximum number of C.dubliniensis have ability to produce protienase 6(66.66%), followed by esterase 5(55.55%), biofilm formation 4(44.44%), haemolysin 2(22.22%) and phospholipase, lipase 1(11.1%) respectively. Conclusion: The result revealed that these enzymes are potential virulence factors are the most important thing to realize pathogenesis of C. dubliniensis.